Pengaruh Bitcoin dan Nilai Tukar Rupiah Terhadap Harga Saham (Studi Pada Sub Sektor Perbankan Yang Terdaftar di Bursa Efek Indonesia Periode 2020-2022) - Ningsih, Sherly Rahma; Wardhani, Rulyanti Susi; Anggita, Wenni (LPPM Institut Pendidikan Nusantara Global, 2024)
Currently, Indonesia is entering an era where technology is developing rapidly and has an impact on various parts of people's lives. This technological development not only has an impact on social and cultural aspects, but also on economic and business aspects. When the Covid-19 pandemic hit Indonesia, it encouraged people to prioritize saving or investing. Investment is expected to be a source of additional income for the community. This research aims to test and analyze the influence of Bitcoin and Exchange on Share Prices in Banking Companies Listed on the Indonesian Stock Exchange in 2020-2022. This research uses quantitative methods. The population in this study are banking companies listed on the Indonesian Stock Exchange. The sample in this research was 29 companies with purposive sampling as a sampling technique. This research uses the panel data regression method and eviews software with a monthly period starting from January 1 2020 to December 31 2022. The results of this research show that cryptocurrency (bitcoin) has a significant positive effect on the share prices of banking companies listed on the Indonesia Stock Exchange, while the rupiah exchange rate has a significant negative effect on the share prices of banking companies listed on the Indonesia Stock Exchange.